Analysis Financial Ratio of Regional Government Budget in Assessing Financial Management Performance of Regional Government of Gianyar Regency - N K C Wandari; K A Bayu Wicaksana; P Adi Suprapto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
This research sought to assess the performance of regional financial management in Gianyar Regency during 2016-2020, as measured by the degree of fiscal decentralization ratio, the regional financial dependence ratio, the Original Regional Government Revenue effectiveness ratio, the regional financial efficiency ratio, and the regional expenditure compatibility ratio. In addition, this research also determined the regional financial capacity of Gianyar Regency, measured through the calculation of Share and Growth, the mapping of regional financial capacity, and the index of regional financial capacity. The research results revealed that the financial management performance of Gianyar Regency during 2016-2020 on average was in a bad condition. It can be seen from its low regional autonomy and its high dependency on the central government. In addition, the regional government has not been able to streamline the regional finances in which regional expenditures were greater than regional revenues. The distribution of regional budget in Gianyar Regency has not been evenly allocated so that the performance regional financial management was at worse state. However, viewed from the level of regional financial capacity, Gianyar Regency has very good potential, obstructed by its low level of Original Regional Government Revenue use to finance regional expenditures..